2023
DOI: 10.1021/jacs.3c06477
|View full text |Cite
|
Sign up to set email alerts
|

Competition between C–C and C–H Bond Fluorination: A Continuum of Electron Transfer and Hydrogen Atom Transfer Mechanisms

Muyuan Wang,
Rozhin Rowshanpour,
Liangyu Guan
et al.

Abstract: In 2015, we reported a photochemical method for directed C–C bond cleavage/radical fluorination of relatively unstrained cyclic acetals using Selectfluor and catalytic 9-fluorenone. Herein, we provide a detailed mechanistic study of this reaction, during which it was discovered that the key electron transfer step proceeds through substrate oxidation from a Selectfluor-derived N-centered radical intermediate (rather than through initially suspected photoinduced electron transfer). This finding led to proof of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…On the basis of the results described above and previous relevant research, it is likely that in situ derived SRD is critical to these reactions. In this regard, based upon the work of Lectka et al, , it is suggested that upon direct photolysis of benzil, an in situ formed triplet state reacts with SF to form benzoyl fluoride, benzoyl radical, and SRD. Aligning with this mechanism the photochemistry and photophysics of benzil and similar diaryl ketones are extremely well documented, while photoexcited benzil is known to undergo efficient intersystem crossing to a long-lived triplet state that is reported to undergo chemical reactions. , Furthermore, the direct photolysis of SF under white light has been shown to lead to N + –F bond homolysis affording SRD.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the basis of the results described above and previous relevant research, it is likely that in situ derived SRD is critical to these reactions. In this regard, based upon the work of Lectka et al, , it is suggested that upon direct photolysis of benzil, an in situ formed triplet state reacts with SF to form benzoyl fluoride, benzoyl radical, and SRD. Aligning with this mechanism the photochemistry and photophysics of benzil and similar diaryl ketones are extremely well documented, while photoexcited benzil is known to undergo efficient intersystem crossing to a long-lived triplet state that is reported to undergo chemical reactions. , Furthermore, the direct photolysis of SF under white light has been shown to lead to N + –F bond homolysis affording SRD.…”
Section: Resultsmentioning
confidence: 97%
“…In a related context, the SF-derived radical dication (SRD) under photochemical conditions is known to mediate HAT or redox events. Furthermore, there is a growing body of work demonstrating that SRD is capable of bond cleavage (e.g., C–H or C–C bond cleavage) and fluorination, depending on the relative energetics of HAT vs single electron transfer (SET) pathways …”
Section: Introductionmentioning
confidence: 99%
“…Characterization of gem-Difluoroalkenyl Compounds. 1- (2,. 1 H NMR (400 MHz, CDCl 3 ) δ 3.86 (s, 3H), 5.68 (dd, J = 26.99, 4.31 Hz, 1H), 6.90 (d,J = 8.28 Hz,1H),6.98 (t,J = 7.55 Hz,1H), (dt, J = 7.70, 1.58 Hz, 1H); 13 C NMR (100.6 MHz, CDCl 3 ) δ 55.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In this chemical space, growing interest in fluorinated compounds and strategies for their streamlined synthesis is of utmost importance. 1,2 In highlighting this status, is an impressive global market of fluorinated compounds, estimated at approximately 20 billion (USD) in the year 2022 and extensive applications in drug development, pharmaceutical synthesis, chemical biology, ion sensing, self-assembly, fluorescence, materials chemistry, and mechanochemistry. 1−3 Prompting much of this attention is the innate makeup of fluorine, e.g., high electronegativity and small ionic radius (1.33 Å), making it the prototypical small atom with a "big ego".…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the context of multistep synthesis of organic compounds with multiple functional groups, cyclic acetals are one of the most well-established and frequently used protective strategies for the carbonyl groups. Moreover, cyclic acetals are used as chiral auxiliaries, present in several bioactive molecules (Figure ), and find wide applications in industrial manufacturing such as fuel additives, surfactants, and flavors . To date, enormous efforts have been dedicated to the development of an efficient system to produce acetals.…”
mentioning
confidence: 99%